2011
DOI: 10.1017/s0956792511000301
|View full text |Cite
|
Sign up to set email alerts
|

Pinned fluxons in a Josephson junction with a finite-length inhomogeneity

Abstract: We consider a Josephson junction system installed with a finite length inhomogeneity, either of microresistor or of microresonator type. The system can be modelled by a sine-Gordon equation with a piecewise-constant function to represent the varying Josephson tunneling critical current. The existence of pinned fluxons depends on the length of the inhomogeneity, the variation in the Josephson tunneling critical current and the applied bias current. We establish that a system may either not be able to sustain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Besides pinning a solution, a defect may also annihilate, rebound, penetrate, or split a (traveling) solution, and it may correspond to a source (or sink) sending out (or absorbing) traveling waves; see, for example, [15,16,31,42,64]. We do not consider these phenomena in the current manuscript.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides pinning a solution, a defect may also annihilate, rebound, penetrate, or split a (traveling) solution, and it may correspond to a source (or sink) sending out (or absorbing) traveling waves; see, for example, [15,16,31,42,64]. We do not consider these phenomena in the current manuscript.…”
mentioning
confidence: 99%
“…However, one may also expect pinned stationary defect solutions in heterogeneous PDEs for which the homogeneous limit does not have a corresponding stationary localized pattern. Typically, there does exist a traveling localized structure in the homogeneous limit in such cases, which indeed gets pinned by the defect and thus corresponds to the stationary solution of the heterogeneous system; see, for example, [15,16,31,41].…”
mentioning
confidence: 99%
“…More examples with N = 1 and N = 2 can be found in [6,22]. This example is similar to the example in [23] and can be related to long Josephson junctions with defects.…”
Section: Lemma 2 ([22 Section 2])mentioning
confidence: 52%
“…Another approximation for this physical reality are inhomogeneities of a tiny length L i and potentials of the form V i (u) = u/L i . In [6], it is shown that the stationary fronts associated with localised homogeneities as described in McLaughlin & Scott [27] can be embedded in the family of stationary waves of finite length inhomogeneities. The stability properties follow from the theory presented in this paper and they regain the criterion derived in [27] (as well as the stability of finite length inhomogeneities).…”
Section: Conclusion and Further Workmentioning
confidence: 97%
See 1 more Smart Citation